ANALISIS PENGARUH HAMBATAN SAMPING TERHADAP KINERJA ARUS LALU LINTAS (STUDI KASUS : JL. JEND. A. YANI KOTA LANGSA) - rizky renaldi (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
AbstractSide friction is a term used to denote the interrelationship between traffic flow and activities along the side of the road. These side barriers often occur on Jalan Jend.A.Yani Kota Langsa, in fact the road is quite dense with shops that use the side of the road as a parking lot and a number of motorized vehicles coming in and out of the side of the road and the flow of vehicles moving slowly. This study uses the MKJI 1997 method which is very effective in planning, operational analysis of traffic, this method can be used to calculate the degree of saturation while other analytical methods can only perform calculations limited to capacity and service levels. Based on the results of side friction analysis in segment I (east direction) of 521.1 events/hour, segment I (west direction) of 526.6 events/hour. In segment II (east direction) 526.8 events/hour and segment II (west direction) 518.1 events/hour and in segment III (east direction) 500.4 events/hour. The three segments are included in the class of very high side resistance (VH). The degree of saturation is obtained from the ratio of traffic volume and road capacity, in each segment the value has a ratio value ≥1, this indicates that each road capacity is saturated and the service level value is in class F with restricted flow, low speed, heavy volume or close to capacity. Keywords— Degree of Saturation, Side Barriers.